Hormonal Assay for Estimation of Progesterone Levels in Normally and Induced Estrus Bitches - Abd-Alhadi, SaifAldeen; Ibrahim, Najlaa Sami S. (The Iraqi Journal of Veterinary Medicine, 2019)
The present study was conducted to measure the concentration of progesterone throughout gestation and parturition in control and treated bitches. Thirty anestrus bitches aged 3 - 6 years and weighing 19.5 - 26 kg were used in this study. The bitches were divided equally into three groups as follows: the 1st group as a control group without treatment, the 2nd group as a treated group anestrus bitches treated orally with 0.125 mg/kg BW bromocriptine (Parlodel) twice daily, and the 3rd group treated orally by 0.012 mg/kg BW cabergoline (Dostinex) until the appearance of estrus signs. The results showed that the number of responded animals were in proestrus bleeding and became pregnant and newborn 70%, 60% and 50% for control, bromocriptine, and cabergoline treated groups, respectively. In addition, there were no significant differences (P ≤ 0.01) in progesterone concentration between the control and treated pregnant bitches. It can be concluded that both medicines bromocriptine and cabergoline have no effect on progesterone levels during pregnancy period in bitches.